Factores sociales y su influencia en el desarrollo de la bronquitis aguda en niños de la parroquia el Salto cantón Babahoyo del primer semestre del 2017 - Calderón Castro, Jorge Gonzalo (2017)
Acute bronchitis is an infectious disease of easy transmission, because the viruses that cause this type of respiratory infections, are sprayed in the air. Many social factors influence the development of acute bronchitis and other respiratory infections, such as poverty, lifestyle, lack of hygiene, poor nutrition, among others. The objective of this project is to promote educational talks based on the social factors that influence in the development of acute bronchitis to reduce its incidence in children of the parish El Salto Canton Babahoyo in the first half of 2017. This project`s study, is within the modality of field, retrospective and transversal because we conducted surveys to the residents of the sector to focus on the main social factors that influence the development of acute bronchitis. Inductive and deductive methods were used in the execution of this quantitative modality project by the statistical analysis that was performed with the study variables. After knowing the results of the surveys, both health personnel and the parents of children with acute bronchitis, it was possible to verify the lack of knowledge about this type of respiratory infections, as well as the influence of some social factors The development of these diseases. Evidently, after analyzing all the data collected, the general hypothesis could be confirmed: If educational talks were promoted based on the social factors that influence the development of acute bronchitis, its incidence would be reduced in children from the parish El Salto Canton Babahoyo in the first half of 2017.